Gene Family Evolution Reflects Adaptation to Soil Environmental Stressors in the Genome of the Collembolan Orchesella cincta. (11th June 2016) - Faddeeva-Vakhrusheva, Anna; Derks, Martijn F. L.; Anvar, Seyed Yahya; Agamennone, Valeria; Suring, Wouter; Smit, Sandra; van Straalen, Nico M.; Roelofs, Dick
Abstract: Collembola (springtails) are detritivorous hexapods that inhabit the soil and its litter layer. The ecology of the springtail Orchesella cincta is extensively studied in the context of adaptation to anthropogenically disturbed areas. Here, we present a draft genome of an O. cincta reference strain with an estimated size of 286.8 Mbp, containing 20, 249 genes. In total, 446 gene families are expanded and 1, 169 gene families evolved specific to this lineage. Besides these gene families involved in general biological processes, we observe gene clusters participating in xenobiotic biotransformation. Furthermore, we identified 253 cases of horizontal gene transfer (HGT). Although the largest percentage of them originated from bacteria (37.5%), we observe an unusually high percentage (30.4%) of such genes of fungal origin. The majority of foreign genes are involved in carbohydrate metabolism and cellulose degradation. Moreover, some foreign genes (e.g., bacillopeptidases) expanded after HGT. We hypothesize that horizontally transferred genes could be advantageous for food processing in a soil environment that is full of decaying organic material. Finally, we identified several lineage-specific genes, expanded gene families, and horizontally transferred genes, associated with altered gene expression as a consequence of genetic adaptation to metal stress. This suggests that these genome features may be preadaptations allowing natural selection to act on. In conclusion, this genome study provides a solid foundation for further analysis of evolutionary mechanisms of adaptation to environmental stressors.